Sequential Use of Carfilzomib and Pomalidomide in Relapsed Multiple Myeloma: A Report from the Canadian Myeloma Research Group (CMRG) Database - Arleigh McCurdy; Christopher P. Venner; Esther Masih-Khan; Martha Louzada; Richard LeBlanc; Michael Sebag; Kevin Song; Victor H. Jimenez-Zepeda; Rami Kotb; Moustafa Kardjadj; Hira Mian; Darrell White; et al. (Current Oncology, 2022)
The treatment of multiple myeloma has dramatically improved due to the availability of novel therapies that are highly effective and are quickly moving into first-line therapy. The Canadian Agency for Drugs and Technologies in Health (CADTH) recently recommended that patients who receive daratumumab should only be eligible to receive either carfilzomib or pomalidomide but not both, for relapsed MM. In order to assess the efficacy of these two agents in the relapsed setting, we utilized our national myeloma database. A total of 121 patients were reviewed, 49 patients received CAR- before POM-based (CAR-POM), and 73 patients received POM- before CAR-based (POM-CAR) therapy. In the groups selected, the median PFS was 4.93 months (95% CI, 2.76–7.07) and 5.36 months (95% CI, 3.75–6.94) for CAR-POM and POM-CAR, respectively. The median OS for patients treated with CAR-POM was 11.01 months (95% CI, 4.50–19.13), and for patients treated with POM-CAR the median OS was 10.98 months (95% CI, 8.98–19.17). In this real-world observational study, we demonstrated that both CAR- and POM-based therapies, irrespective of the order in which they were used, were effective treatment options for patients with advanced relapsed MM.